2019
DOI: 10.1038/s41378-019-0101-2
|View full text |Cite
|
Sign up to set email alerts
|

Displacement Talbot lithography for nano-engineering of III-nitride materials

Abstract: Nano-engineering III-nitride semiconductors offers a route to further control the optoelectronic properties, enabling novel functionalities and applications. Although a variety of lithography techniques are currently employed to nano-engineer these materials, the scalability and cost of the fabrication process can be an obstacle for large-scale manufacturing. In this paper, we report on the use of a fast, robust and flexible emerging patterning technique called Displacement Talbot lithography (DTL), to success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 69 publications
0
41
0
Order By: Relevance
“…Optimized thermal etching parameters were then used for further experiments on various mask configurations created on c-plane and (1122) semi-polar GaN templates. A detailed description of the dielectric mask fabrication process can be found in the Methods section and our previous publication 33 , while SEM images of the SiN x openings are shown in Fig. S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Optimized thermal etching parameters were then used for further experiments on various mask configurations created on c-plane and (1122) semi-polar GaN templates. A detailed description of the dielectric mask fabrication process can be found in the Methods section and our previous publication 33 , while SEM images of the SiN x openings are shown in Fig. S1.…”
Section: Resultsmentioning
confidence: 99%
“…However, the process was reported to be strongly sensitive to threading defects, resulting in the formation of pores under the mask and, therefore, with a poor organization of nanoholes overall and poor uniformity of the nanohole dimensions. More recently, Damilano and co-authors reported several works on the selective area sublimation (SAS) of nanorods and nanoholes having a straight sidewall profile, achieved in a molecular beam epitaxy (MBE) chamber either from a SiN x self-organized mask 15,31 , or a SiN x nanopatterned mask 32,33 . With their conditions, nanorods and nanoholes with a high organization and fairly uniform dimensions were successfully achieved 32,33 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a metal mask is preferred to obtain high aspect ratio structures by deep plasma etching. While displacement talbot lithography can pattern thick resist at the nanoscale 30 , it is still an emerging technique with a resolution limited by the wavelength illumination source, often 365 nm 30 or 266 nm 31 , while NIL resolution can be scaled further down.…”
Section: Openmentioning
confidence: 99%
“…2.5D structures can be created using 2-photon lithography [40]. For diffractive structures, special techniques can prove successful, such as interference lithography [45] and Talbot lithography [46], which are uniquely suited to produce periodic structures.…”
Section: Diamond Micro-and Nanofabricationmentioning
confidence: 99%